Flow Cytometry in the Diagnosis of Canine B-Cell Lymphoma - Riondato, Fulvio; Comazzi, Stefano (Frontiers in Veterinary Science, 2021)
B cell lymphoma (BCL) is a heterogenous group of lymphoid malignancies representing the majority of canine lymphomas. Diffuse large B cell lymphoma is the most diffuse canine lymphoma subtype but other subtypes (marginal zone lymphoma, follicular lymphoma, mantle cell lymphoma, etc) have been described in the dog. This review aims to explore the use of flow cytometry for refining the diagnosis of canine BCL, with particular emphasis for the possible identification of some peculiar immunotypes, the investigation of putative prognostic markers, and the role of flow cytometry for the evaluation of lymphoma stage and minimal residual disease.